Social Media Use and Entrepreneurial Intention: The Role of Students' Entrepreneurial Self-Efficacy - Nur Ika Effendi; Risni Nelvia; Yopi Eka Anroni; Isman Isman; Wahyu Faisa Rika Sandi (PT. Anagata Sembagi Education, 2025)
Digitalization can change the mindset and the way students access information, as well as their desire to start a business or their interest in entrepreneurship. This study aims to determine the effect of social media on students' intention in entrepreneurship, with self-efficacy as an intervening variable, among students at Muara Bungo University. The study employed a quantitative approach, utilizing questionnaires to collect data from 101 students selected from all active students in the even semester of the 2024/2025 academic year, via proportionate stratified random sampling. Based on data processing Smart-PLS 4 statistical tool, the study found that social media and self-efficacy have a positive and significant effect on entrepreneurial interest, partial and simultaneous. Self-efficacy partially mediates the relationship between social media and entrepreneurial interest. It is hoped that universities, especially Muara Bungo University, can strengthen self-efficacy development programs and utilize social media as a learning tool to increase students' interest in entrepreneurship. This approach can help students create jobs in the future and increase economic growth in Bungo Regency.